1990
DOI: 10.1159/000177581
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Defective in vivo Synthesis of Mitochondrial Proteins on Cellular Biochemistry and Physiology of Malnourished Rats

Abstract: Investigations were carried out to find the biochemical and bioenergetic implications of a defective in vivo synthesis of mitochondrial proteins during dietary-protein depletion. 3.4% dietary protein was fed to 21-day-old weanling rats for 30 days (experimental), while 21.0% dietary protein was fed to controls. A close simulation of marasmic-kwashiorkor syndrome was obtained in the experimental group. Rat liver mitochondria were isolated, and the functional and structural integrity was determined using biochem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 15 publications
1
5
0
Order By: Relevance
“…The PPARα induction of peroxisomal biogenesis and stimulation of mitochondrial FAO was sufficient to ameliorate hepatic steatosis and remarkably restore hepatic energy status and albumin synthesis suggesting a link between the peroxisomal and mitochondrial dysfunction, and liver health during malnutrition. Our study expands the understanding of early observations that suggested impairment of mitochondrial bioenergetic functions in livers of severely malnourished rats [30,31] and humans [32] and postulated a link between the loss of peroxisomal function and development of a fatty liver in severe malnutrition [33] Translating the animal model to the clinical phenotype of malnutrition Two clinical phenotypes of severe malnutrition exist. Marasmus is defined by clinical wasting, while kwashiorkor is typically accompanied by more complex characteristics such as 21 pitting edema, hair discoloration, skin lesions and hepatomegaly, although considerable overlap with marasmus often exists.…”
Section: Discussionsupporting
confidence: 55%
“…The PPARα induction of peroxisomal biogenesis and stimulation of mitochondrial FAO was sufficient to ameliorate hepatic steatosis and remarkably restore hepatic energy status and albumin synthesis suggesting a link between the peroxisomal and mitochondrial dysfunction, and liver health during malnutrition. Our study expands the understanding of early observations that suggested impairment of mitochondrial bioenergetic functions in livers of severely malnourished rats [30,31] and humans [32] and postulated a link between the loss of peroxisomal function and development of a fatty liver in severe malnutrition [33] Translating the animal model to the clinical phenotype of malnutrition Two clinical phenotypes of severe malnutrition exist. Marasmus is defined by clinical wasting, while kwashiorkor is typically accompanied by more complex characteristics such as 21 pitting edema, hair discoloration, skin lesions and hepatomegaly, although considerable overlap with marasmus often exists.…”
Section: Discussionsupporting
confidence: 55%
“…These authors reported a diminished respiratory control ratio and a drastic reduction in the basal enzymatic activities (such as ATPase and cytochrome c oxidase) with low ATP production in mitochondria of different tissues of protein-deficient rats. This led to bioenergetic consequences, such as dependence on glycolysis and other biochemical aberrations (6).…”
Section: Discussionmentioning
confidence: 99%
“…Digestion disorders with diarrheic symptoms are accompanied by altered redox and energetic mitochondrial processes. These impairments are evidenced by a reduced respiratory control ratio and changes in enzymatic activities, such as adenosine triphosphate synthase (ATPase), cytochrome oxidase, lactate dehydrogenase, succinate dehydrogenase, and alkaline phosphatase (5)(6)(7).…”
mentioning
confidence: 99%
“…Kwashiorkor, a disease caused by protein deficiency, has been associated with multiple adverse effects including -among others -hepatic steatosis, an almost total absence of peroxisomes, mitochondrial dysfunction, and oxidative stress (46,50,106,126). Recently, it was reported that feeding weanling rats a low protein diet yielded a similar phenotype, and that treating these animals with fenofibrate resulted in peroxisome reappearance, restoration of mitochondrial fitness, and amelioration of the hepatic phenotype (165).…”
Section: Kwashiorkormentioning
confidence: 99%